2016
DOI: 10.22610/jebs.v8i4(j).1366
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Fashion Adoption among the Youth in Johannesburg, South Africa

Abstract: Fashion in Africa has undergone a tremendous transformation process due to an increase in international trade. As a result, African consumerism has surfaced. Through being part of the global community, the youth in Africa capitalizes on the wide variety of fashions available, and they view fashion as a medium for expressing their identity. More specifically, in South Africa, fashion is used as the ideal vehicle for the youth to re-map previously fixed racial identities. Although a number of studies have explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Previous studies found differences across gender in fashion involvement, fashion consciousness, and reference group influences in South Africa (Kolatsis, 2017;Venter et al, 2016;Tshabalala, 2014;Kotzé et al, 2012,). However, very limited research exists on differences within male fashion leadership groups, particularly between fashion innovators and fashion opinion leaders and the driving forces behind their shopping for fashion in the South African context.…”
Section: Male Consumers' Fashion Behavior In the South African Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found differences across gender in fashion involvement, fashion consciousness, and reference group influences in South Africa (Kolatsis, 2017;Venter et al, 2016;Tshabalala, 2014;Kotzé et al, 2012,). However, very limited research exists on differences within male fashion leadership groups, particularly between fashion innovators and fashion opinion leaders and the driving forces behind their shopping for fashion in the South African context.…”
Section: Male Consumers' Fashion Behavior In the South African Marketmentioning
confidence: 99%
“…Prinsloo (2015) highlights the growing trend in South African males' interest and involvement in shopping for clothing. Especially, younger males (under 45 years) in South Africa are more involved in fashion purchasing and tend to be more fashion conscious than their older counterparts (Venter et al, 2016;Tshabalala, 2014). Moreover, South African males are price and brand conscious when shopping for clothing (Van Belkum, 2016).…”
Section: Male Consumers' Fashion Behavior In the South African Marketmentioning
confidence: 99%
“…According to Junarsin, Pangaribuan, Wahyuni, Hidayat, Putra, Maulida and Soedarmono (2022), brand preference is the equivalent of purchase intention and a consumer's attitude towards a brand plays an important role in determining brand preference. Preference for a brand has generally been considered to be a direct precursor of purchase intention (Venter, Chinomona & Chuchu, 2016). Interestingly, Bashir, Faheem, Hassan and Shaikh (2019) mentioned that brand equity reflects brand preference, and that brand preference and purchase intention are related in a similar manner.…”
Section: Brand Preference and Purchase Intentionmentioning
confidence: 99%
“…Jordaan et al [20] measured consumer innovativeness by using the domain-specific innovativeness (DSI) scale developed by Goldsmith and Hofacker [21], instead of using Rogers' time-of-adoption method, since it is difficult to know the exact time of the introduction and the purchase of a new product in a specific market. Venter et al investigated the influence of fashion consciousness, the need for uniqueness, susceptibility to interpersonal influence, collectivism/individualism, and masculinity/femininity on fashion adoption [22]. Workman et al identified the differences between consumer groups in their need for uniqueness [13,23].…”
Section: Introductionmentioning
confidence: 99%